2024
DOI: 10.1101/2024.03.22.586316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell epigenomic dysregulation of Systemic Sclerosis fibroblasts via CREB1/EGR1 axis in self-assembled human skin equivalents

Tamar R. Abel,
Noelle N. Kosarek,
Rezvan Parvizi
et al.

Abstract: Systemic sclerosis (SSc) is an autoimmune disease characterized by skin fibrosis, internal organ involvement and vascular dropout. We previously developed and phenotypically characterized an in vitro 3D skin-like tissue model of SSc, and now analyze the transcriptomic (scRNA-seq) and epigenetic (scATAC-seq) characteristics of this model at single-cell resolution. SSc 3D skin-like tissues were fabricated using autologous fibroblasts, macrophages, and plasma from SSc patients or healthy control (HC) donors. SSc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 123 publications
0
1
0
Order By: Relevance
“…We have also demonstrated that RUNX1 is hypomethylated in the SSc-derived fibroblast genome, indicating that the increased RUNX1 expression observed in SSc patients is likely due to dysregulation at the epigenetic level. Using a single-cell multiomic analysis, in a separate study, we showed that RUNX1 is consistently enriched in a subpopulation of fibroblasts in an SSc-derived self-assembled skin-equivalent (saSE) tissue model at levels similar to those observed in SSc skin biopsies 45 . In an analysis of single-cell sequencing assay for transposase-accessible chromatin (scATAC-seq), a fibroblast subpopulation was identified by elevated TF motifs for RUNX1 and RUNX2 , together with SMAD3 , SMAD5 , and NFKB1 .…”
Section: Discussionmentioning
confidence: 85%
“…We have also demonstrated that RUNX1 is hypomethylated in the SSc-derived fibroblast genome, indicating that the increased RUNX1 expression observed in SSc patients is likely due to dysregulation at the epigenetic level. Using a single-cell multiomic analysis, in a separate study, we showed that RUNX1 is consistently enriched in a subpopulation of fibroblasts in an SSc-derived self-assembled skin-equivalent (saSE) tissue model at levels similar to those observed in SSc skin biopsies 45 . In an analysis of single-cell sequencing assay for transposase-accessible chromatin (scATAC-seq), a fibroblast subpopulation was identified by elevated TF motifs for RUNX1 and RUNX2 , together with SMAD3 , SMAD5 , and NFKB1 .…”
Section: Discussionmentioning
confidence: 85%